High Responsivity, Broadband, and Fast Graphene/Silicon Photodetector in Photoconductor Mode. Issue 9 (12th May 2015) - Chen, Zefeng; Cheng, Zhenzhou; Wang, Jiaqi; Wan, Xi; Shu, Chester; Tsang, Hon Ki; Ho, Ho Pui; Xu, Jian‐Bin
<x xml:space="preserve">Abstract</x> A fast‐response photodetector is developed, which is highly photoresponsive and works over a broadband. It is fabricated using a combination of chemical vapor deposition graphene and silicon, together with the utilization of a lateral photoconductor operating mode. The photodetector exhibits high responsivities of ≈1.0 × 104 and ≈0.23 A W−1 in the visible (632 nm) and infrared regions (1550 nm), respectively. The response time is both below 3 μs in both spectral regions.